Kegiatan KMFEB Foundation 2022 : Pendampingan Belajar, Donasi Buku, Lomba Cipta Baca Puisi dan Storytelling, Talkshow - Puspitararas, Della Nanda; Ilmi, Faza Bahrul; Haqqania, Shafira; Aqliyah, Siti Nurfarida Mar'atul; Istiqomah, Istiqomah (Darma Sabha Cendekia, 2023)
As prospective leaders, students must possess social consciousness. Therefore, students of the Faculty of Economics and Business at Jenderal Soedirman University engage in annual community service through the Keluarga Mahasiswa FEB (KMFEB) Foundation. In 2022, the KMFEB Foundation host four series of events, including study aid, book donation, storytelling and poetry writing-reading contests, and talkshow. Study assistance was provided at the orphanages of Roudlotul Jannah Patikraja and Darmo Yuwono Purwokerto, and SDN 01 Watujaran. Donors and benefactors are solicited for book donations. High school/vocational school students from the entire Banyumas Regency participated in storytelling and poetry reading competitions, while the talk show intended to motivate and inspire participants to become "heroes". This activities helps students develop their social awareness and delicate skills. For collaborators, particularly orphanages and schools, students and orphans are more inspired to study and motivated to pursue higher education. For contestants, their talents and interests can be exploited, while talk show participants are inspired to contribute to the advancement of their respective communities.